2017
DOI: 10.2196/mhealth.8288
|View full text |Cite
|
Sign up to set email alerts
|

Time Gain Needed for In-Ambulance Telemedicine: Cost-Utility Model

Abstract: BackgroundStroke is a very time-sensitive pathology, and many new solutions target the optimization of prehospital stroke care to improve the stroke management process. In-ambulance telemedicine, defined by live bidirectional audio-video between a patient and a neurologist in a moving ambulance and the automated transfer of vital parameters, is a promising new approach to speed up and improve the quality of acute stroke care. Currently, no evidence exists on the cost effectiveness of in-ambulance telemedicine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Even with these limitations, we can conclude that there is clear evidence that centralization is economically wise. Several authors have shown that teleemergency systems are effective from a medical perspective [ 22 24 ] as well as efficient from an economic [ 25 , 26 ] perspective. Our analysis strongly underlines that the efficiency strongly increases if the teleemergency doctor offices are centralized, but at least under German conditions of federalism, centralization is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Even with these limitations, we can conclude that there is clear evidence that centralization is economically wise. Several authors have shown that teleemergency systems are effective from a medical perspective [ 22 24 ] as well as efficient from an economic [ 25 , 26 ] perspective. Our analysis strongly underlines that the efficiency strongly increases if the teleemergency doctor offices are centralized, but at least under German conditions of federalism, centralization is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review identified 47 papers that met the inclusion criteria (32 primary studies 39,41, and 15 reviews 16,39,40,47,48,53,[89][90][91][92][93][94][95][96][97] ; for details, see Appendix 1, Table 11). One record was a trial registration; 98 this led to the identification of a research paper, 80 which was included in place of the trial registry record.…”
Section: Phase 2: Systematic Reviewmentioning
confidence: 99%
“…'Prehospital telestroke'/'mobile telemedicine' is therefore identified as a promising, novel development to support clinical examination in the field by EMS clinicians, with remote support provided from hospital-based staff and stroke experts. 16,[39][40][41] This topic was the focus of a two-phase literature review, which we outline below. Phase 1 of the review was used to inform the design of research materials in our rapid evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…RenderX telecommunication specialists have developed devices in cooperation with rescue service personnel, emergency physicians, and emergency departments. These devices have also been trialed in test operations to evaluate their effectiveness and safety in regular operations [37][38][39][40]. One example is the Aachen TEP system.…”
Section: Xsl • Fomentioning
confidence: 99%